O som das Fontainhas: uma análise da banda sonora de três filmes de Pedro Costa - Oliveira, Luiz Fernando Coutinho de (2020)
This research analyzes the film sound of three works by Portuguese filmmaker Pedro Costa, namely Bones (1997), In Vanda’s Room (2000) and Colossal Youth (2006), which together compose what is commonly referred to as “Fontainhas’ Trilogy”. These films, which describe the filmmaker’s peculiar trajectory in relation to the neighborhood of Fontainhas, in the Metropolitan Region of Lisbon, are all studied based on an investigation of their sound design’s significations. In order to demonstrate the specific importance of the soundtrack in the cinema of Pedro Costa, soundtrack here understood as constituted by dialogues, noises and music and their relationships with the images, we analyze: a) the different impressions of silence that the films produce, since these impressions are perceived as products of certain sound and image dispositions; b) the different acousmatic sounds constituted within the films, especially their effects on the images and vice-versa; and c) the different voices that manifest themselves in the films, extending the analysis to dialogues, monologues and songs. The study of the three films and their soundtracks allows us to conclude that not only film sound is an essential element to Pedro Costa’s cinematographic style, but also that the conception and creative use of sounds are closely related to the production method which the filmmaker discovers and matures from film to film.